STRENGTHENING THE MORALS OF THE MUSLIM GENERATION THROUGH DIGITAL-BASED ISLAMIC EDUCATION - Abdul Wahab Syakhrani; Muhammad Nur Effendi; Agus Fawait; Nur Aini Bunyani; Abdonia W. Finmeta (CV. ADIBA AISHA AMIRA, 2023)
This literature study explores the potential of digital-based Islamic education in strengthening the moral character of Muslim youth. Reviewing existing literature on the topic, this study highlights the benefits and challenges of incorporating digital technologies in Islamic education. It presents strategies for effectively utilizing these tools to promote moral development. The literature review results suggest that digital-based Islamic education can provide a flexible and accessible platform for students to engage with Islamic teachings and develop their moral reasoning. Digital technologies such as online modules, interactive simulations, and social media platforms can deliver Islamic education to a broader audience, including those unable to attend traditional Islamic schools or mosques. However, the study also identified several challenges in implementing digital- based Islamic education, such as the need for proper regulation and oversight, concerns about the quality of online content, and the potential for technology to promote superficial engagement with Islamic teachings. To overcome these challenges, the study recommends that educators and developers of digital Islamic education programs prioritize integrating interactive and reflective learning activities, provide opportunities for direct experiences and community engagement, and emphasize developing critical thinking and moral reasoning skills. Additionally, regulatory bodies and Islamic institutions should establish guidelines and standards for digital-based Islamic education to ensure the quality and accuracy of online content. Overall, this literature study suggests that digital-based Islamic education can be an effective tool for strengthening the moral character of Muslim youth. However, it requires careful planning and thoughtful implementation to realize its potential fully.